EXPORT OF TOURIST SERVICES OF BELARUS TO CHINA - Holubeu, Siarhei; Suhak, Vadzim; Avsyuk, Andrey; Chen, Jianbo (Economy and Sociology, 2023)
The article discusses the institutional foundations of mutually beneficial Belarusian-Chinese tourism cooperation. The research aims to explore the state, problems, and prospects for the development of the tourism industry in China and Belarus and to develop proposals for the development of tourism export services to China. The authors examine the structure of the tourism industry in Belarus and China, the inductive prerequisites for the development of the tourism sector of the two countries, as well as global trends in the field of tourism related to the COVID-19 pandemic. Special attention was paid to developing promising types of tourism in Belarus and China, such as "red," rural, folklore, digital, and “winter” tourism. The case of the Republic of Belarus, which may be helpful for Central and Eastern Europe countries, illustrates the possible directions for the growth of tourism export services to China, thanks to the optimisation of measures to prevent and control COVID-19. This optimisation contributed to the cross-border movement of Chinese citizens and opened up opportunities to attract Chinese tourists to the Belarusian market and the markets of Central and Eastern Europe. We have emphasised that for Belarus, achieving significant results in the development of the export of tourist services to China involves solving some essential tasks: conducting large-scale and ongoing advertising and informational campaigns to increase the awareness of foreign audiences about tourism products and recognition of the country as an attractive tourist destination; development and implementation of an incentive system for tour operators from China; performance of activities to adapt the service in hotels, airports, train stations, restaurants, museums to the individual characteristics and specific needs of tourists from China; improving the tax-free system to increase the interest of citizens from China in visiting Belarus.